In-situ epoxidation of castor oil with applied novel sulfate-impregnated zeolite catalyst - Addli, Mohammad Aathif; Jalil, Mohd Jumain; Azmi, Intan Suhada; Md Rasib, Ismail (UiTM Cawangan Johor Kampus Pasir Gudang, 2025)
This study focuses on the in-situ epoxidation of non-edible vegetable oil, specifically castor oil, using a novel sulfate-impregnated zeolite catalyst. The research addresses the growing need for environmentally friendly and sustainable alternatives to traditional epoxidation methods, which often involve hazardous reagents and produce unwanted byproducts. By combining a heterogeneous catalytic process with non-edible castor oil, this innovative approach minimizes waste generation while enhancing the epoxidation efficiency. The developed sulfate-impregnated zeolite catalyst offers several unique advantages, including high catalytic activity and selectivity toward epoxide formation. The in-situ process reduces the need for external oxidants, thereby streamlining the reaction and lowering operational costs. Compared to conventional methods, this technology is eco-friendly, energy-efficient, and economically viable. The socio-economic and environmental impact of this innovation is significant. By utilizing non-edible vegetable oils like castor oil, it avoids competition with the food supply chain, promoting sustainability and supporting local agricultural industries. The epoxidized products derived from this process, such as bio-based resins and plasticizers, serve as green alternatives in automotive, construction, and coating industries, reducing dependence on petroleum-based chemicals and contributing to a lower carbon footprint. The commercialization prospects are promising due to the increasing demand for sustainable and bio-based chemicals in global markets. This novel catalytic process can be scaled up for industrial applications, offering cost-effective production of epoxides while addressing environmental concerns